KAJIAN MORFOLOGI IKAN SILI PADA NASI BORANAN MAKANAN KHAS DAERAH LAMONGAN PROVINSI JAWA TIMUR - Yustika Aulia Rahma (Jurnal Matematika dan Sains (JMS), 2021)
Boranan rice is a traditional and typical food from the Lamongan city and can only found in the Lamongan area. Boranan rice, consisting of rice, spices, side dishes, and peanut crips; which is a type of cracker made from rice flour with seasoned and fried. One of special side dish from Boranan Rice is smoked Sili Fish. Sili Fish is a tropical river fish that usually used to ornamental fish and also cosumed by Lamongan people. The purpose of this study was to identify the type of Sili Fish that used as a complement to boranan rice and to describe the history of Sili Fish that used for side dishes of boranan rice. The research was conducted using interviews and direct field observations. The type of Sili fish used in the side dish of boranan rice is Macrognathus aculeatus (Order: Synbranchiformes, Family: Matacembelidae). Sili fish is used as a typical side dish of boran rice because no community has yet processed sili fish as food, so that the Lamongan people, especially those who sell boran rice, take advantage of the presence of sili fish which is found in the Bengawan Solo river by making it a special side dish in boran rice.